PENGARUH SUNSET POLICY, TAX AMNESTY, DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK - Mona Zahroh (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2020)
Zahroh, Mona. 2018.Influence Of Sunset Policy, Tax Amnesty, and Tax Sanction on Taxpayer Compliance Case Study in the West Sidoarjo Tax Sevice Office.This thesis is not published Faculty of Economics and Business of Muhammadiyah University of Sidoarjo. The purpose of this study was to determine the effect of Sunset Policy, Tax Amnesty, and Tax Sanctions on Taxpayer Compliance Case Study in the West Sidoarjo Tax Service Office. Sunset Policy, Tax Amnesty, and Tax Sanctions became the independent variables in this study, while Taxpayer Compliance became the dependent variable.The population taken in this study is Taxpayers at the Primary Sidoarjo Tax Service Office as many as 68 respondents. The sampling technique used was purposive sampling from 73 questionnaires distributed, obtained 68 respondents who could be include in data processing. Data analysis in this study using multiple linear regression with the help of SPSS program (Statistical Program for Social Science) version 16 software to process questionnaire data.The results showed that Sunset Policy has an influence on Taxpayer Compliance with a Significant value of 0,001, Tax Amnesty has an influence on Taxpayer Compliance with a significant value of 0,000, Tax Sanctions have an influence on Taxpayer Compliance with a significant value of 0,016.